Proses Produksi Batik Pewarna Alam di Batik Jalidin Masaran Sragen - Dafi Setiyanto; Figur Rahman Fuad (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2024)
Indonesia has abundant natural wealth spread throughout Indonesia. Natural wealth provides various benefits for daily life, one of which is for batik craftsmen from Sragen district. Taking advantage of Indonesia's natural wealth, one of the craftsmen from Sragen district was able to develop batik using natural dyeing techniques. Natural dyes taken from certain plant extracts will produce dyes for batik coloring. This research was conducted with the aim of seeing the batik production process with natural dyes and knowing the tools and materials used in the batik production process with natural dyes. The method used in this research is training and group discussion forums related to the natural dyed batik production process. The results of this research are several batik works with a natural dyeing process that uses natural dyes such as indigofera, tingi, jalawe, and jambal.